CAV1 alleviated CaOx stones formation via suppressing autophagy-dependent ferroptosis - Yuanyuan Yang; Senyuan Hong; Yuchao Lu; Qing Wang; Shaogang Wang; Yang Xun (PeerJ, 2022)
Background Calcium oxalate (CaOx) is the most common type of kidney stone, but the mechanism of CaOx stones formation remains unclear. The injury of renal cells such as ferroptosis and autophagy has been considered a basis for stones formation. Methods We conducted transmission electron microscope (TEM), reactive oxygen species (ROS), malondialdehyde (MDA), glutathione (GSH), and C11-BODIPY analysis to explore whether CaOx could induce autophagy-dependent ferroptosis in vivo and in vitro. To explore the possible mechanism, we conducted bioinformatic analysis of patients with or without CaOx stones, Western blot and qPCR were used to identify the different genes we found in bioinformatic analysis. Results In our study, we found that CaOx could induce autophagy-dependent ferroptosis no matter in vivo or in vitro, which might finally lead to urolithiasis. Bioinformatic analysis of the GSE73680 dataset indicated that the expression of caveolin-1 (CAV1) was higher in control patients than CaOx stone patients, the STRING database indicated that CAV1 might interact with low density lipoprotein receptro-related protein 6 (LRP6), Gene Set Enrichment Analysis (GSEA) showed that the WNT pathway positively associated with the control group while negatively related to the stone group, and LRP6 was the core gene of the WNT pathway. Western blot found that CAV1, LRP6, and Wnt/β-Catenin were decreased in Human Kidney2 (HK2) cells stimulated with CaOx. Furthermore, the WNT pathway was considered to be involved in autophagy and ferroptosis. Conclusions We presumed that CAV1 could ameliorate autophagy-dependent ferroptosis through the LRP6/Wnt/β-Catenin axis, and finally alleviate CaOx stone formation.